Picoline based fluorescence 'turn-on' chemosensor for zinc(II) ion recognition, cell imaging and cytotoxicity study: Synthesis, crystal structure, spectroscopy and DFT. (1st December 2020) - Jana, Abhimanyu; Aher, Abhishek; Brandao, Paula; Ali, Syed Samim; Samanta, Sandip Kumar; Mondal, Gopinath; Bera, Pradip; Santra, Ananyakumari; Manna, Sunil Kumar; Mahapatra, Ajit Kumar; Bera, Pulakesh
Graphical abstract: A picoline based 'turn-on' chemosensor (L ) and it's zinc(II) complex, Zn(L)2 (1 ) have been synthesized and structurally characterized. The detection limit (0.36 µM) and association constant (log Kapp  = 13.25) are evaluated by the fluorescence experiment. The probe shows reversibility in addition of dihydrogen phosphate (H2 PO4 − ) ion to the 1 . The probe has sufficient cell permeability and intracellular Zn(II) imaging property. Both L and 1 are innocuous against PBMC (peripheral blood mononuclear cells) but effective antitumor agents against U-937 cancer cells. Highlights: Synthesis and structure of a highly selective and sensitive picoline based small molecule (Mol. Wt. 254). A 'turn on' fluorescent probe with Zn(II) in HEPES buffer. Excellent bleaching of fluorescence in H2 PO4 − to the Zn-complex. Ligand has sufficient cell permeability and intracellular Zn(II) sensing property. Compounds are innocuous against PBMC but effective antiproliferative against U-937 cancer cells. Abstract: A new picoline based ligand, namely 2-hydroxy-5-methyl-3-[{(6-methylpyridin-2-yl)imino}methyl]benzaldehyde (L ) and it's zinc(II) complex, Zn(L)2 (1 ) have been synthesized and structurally characterized. The ligand (L ) selectively interacts with Zn 2+ ion in presence of series of cations in CH3 CN-H2 O (v/v 1:1) in 1 mM HEPES buffer (pH 7.2). The fluorescence intensity of L is significantly enhanced, and it is increased to 52 times on coordination with Zn(II) ion. The fluorescence intensity value of the L does not show any significant change in the pH range 5 to 9, while the extent of emission phenomenon with Zn(II) ions is observed in the said pH range. The detection limit (0.36 µM) and association constant (log Kapp  = 13.25) are evaluated by the fluorescence emission experiment. The probe shows reversibility in addition of dihydrogen phosphate (H2 PO4 − ) ion to the 1 . Additionally, the 'turn-on' fluorescence probe has sufficient cell permeability and intracellular Zn(II) sensing property as envisaged from the microscopic imaging in HEK293T cells. Both L and ZnL2 (1) are innocuous against PBMC (peripheral blood mononuclear cells) but effective antitumor agents against U-937 cancer cells.